DETERMINATION OF ACCOUNTABILITY FOR LIQUIDITY OF DEBT IN THE RAMBU SOLO’ - Totanan, Chalarce; Paembonan, Laendatu; Kekka, Gabriella Pingkan; Rombe, Elimawati (Universitas PGRI Madiun, 2023)
ABSTRACTThis study aims to examine and analyze the determination of accountability on the liquidity of rambu solo’ debt. The research population is members of the Toraja community who live in Palu City. Samples were taken purposively, and 150 people of Toraja lived in Palu City. Who are get in Perhimpunan Masyarakat Toraja Indonesia (PMTI). Data were obtained through questionnaires that were distributed directly to respondents. The results showed that determining loving-kindness and socio-cultural accountability affected debt liquidity in the rambu solo’ culture. In contrast, physical accountability did not affect debt liquidity in the rambu solo’ culture.ABSTRAKPenelitian ini bertujuan untuk menguji dan menganalisis penentuan akuntabilitas likuiditas utang rambu solo’. Populasi penelitian adalah anggota masyarakat Toraja yang berdomisili di Kota Palu. Sampel diambil secara purposif sebanyak 150 orang masyarakat Toraja yang tinggal di kota Palu. Yang tergabung dalam Perhimpunan Masyarakat Toraja Indonesia (PMTI). Data diperoleh melalui kuesioner yang dibagikan langsung kepada responden. Hasil penelitian menunjukkan bahwa penentuan akuntabilitas cinta kasih dan akuntabilitas sosial budaya berpengaruh terhadap likuiditas utang pada budaya rambu solo’, sedangkan akuntabilitas fisik tidak berpengaruh terhadap likuiditas utang pada budaya rambu solo’.